Linear stability analysis for severe slugging: sensitivity to void fraction and friction pressure drop correlations. (2017) - Azevedo, Gabriel Romualdo De; BaliÁ±o, Jorge Luis; Burr, Karl Peter
In this paper a numerical linear stability analysis is performed on a mathematical model for the two-phase flow in a pipeline-riser system. Void fraction is a key variable, as it influences the mixture properties and slip between the phases. Friction two-phase pressure drop is also an important variable as it is necessary, for instance, to determine the pumping power in multiphase processes. For a correct prediction of the stability behaviour of a pipeline-riser flow, preventing the occurrence of severe slugging, it is important to assess the sensitivity of the system response to different void fraction and friction pressure drop correlations. Three void fraction (Bendiksen, 1984; Chexal et al., 1997; Bhagwat and Ghajar, 2014) and two friction pressure drop correlations [homogeneous and Müller-Steinhagen and Heck (1986)] are implemented. The resulting stability maps and state variables profiles for vertical risers are compared for the different correlations. For the void fraction sensitivity study, results show that the different correlations give similar stability maps, with very small differences in the near horizontal branch (low gas superficial velocities) of the stability boundary and slight differences in the near vertical branch (low liquid superficial velocities). For the friction pressure drop sensitivity study, results show that it does not affect significantly the stability maps because the mass fluxes are low and the main contribution to the total pressure drop comes from the gravitational term. The different correlations show the right experimental trend by increasing the unstable region as the equivalent buffer length in the pipeline is increased.